Comparative study of representations of professional autonomy produced by first and last-period undergraduate nursing students - Érick Igor dos Santos; Antonio Marcos Tosoli Gomes; Sergio Corrêa Marques; Raquel de Souza Ramos; Aline Cerqueira Santos Santana da Silva; Francimar Tinoco de Oliveira (Universidade de São Paulo, 2017)
ABSTRACT Objective: to compare the social representations of professional nurse autonomy produced by first and last-period undergraduate nursing students. Method: qualitative, descriptive and exploratory study, based on the structural approach of social representations, the Central Core Theory, carried out with 171 students from three federal public universities, using the free association technique on the object "professional nurse autonomy". The data were submitted to EVOC 2005 software and to similarity analysis. Results: care was the central core of the representational structure identified among the students of the first period. Among last-period students, knowledge stood out as a core element. The term responsibility was identified as common to both central cores. Conclusion: regarding professional autonomy, the results point to an overlapping process of the reified and consensual universes during the undergraduate course. However, responsibility, inherent in the profession, remains cross-sectional. For the first period students, autonomy is resignified in a practical and attitudinal way, whereas for the last period students, the knowledge acquired stimulates them to assign meaning to professional autonomy with a cognitive and attitudinal representation. The data can support the use of innovative teaching practices in nursing undergraduate courses.